Evaluating Knowledge, Practice, and Barriers to Informed Consent Among Professional and Staff Nurses in South Africa: An Empirical Study - Chima, Sylvester (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled)
Background: Informed consent (IC) is an ethical and legal obligation protected by constitutional rights to bodily integrity, well-being, and privacy in South Africa. The National Health Act 2003 codified IC regulations, requiring that all healthcare professionals inform patients about diagnosis, risks, benefits, options, and refusal rights while factoring in patients’ language and literacy levels. Objectives: This study’s primary aim was to determine the extent of South African professional/staff nurses’ compliance with current IC regulations and ascertain socio-cultural impediments impacting proper IC practice. Methods: A cross-sectional survey using semi-structured questionnaires was used to evaluate knowledge and practice of IC among nurses in KwaZulu-Natal province. Data were analyzed using SPSS, v.21. Descriptive statistics, chi-squared tests, and content analysis were used to compare nursing domains. Results: Three hundred fifty-five (355) nurses, 92% females, with 1 to 41 years of professional experience, completed this study. Information disclosed by nurses to patients included diagnosis (77%), treatment benefits (71%), risks (69%), recommendations (65%), risks of refusal (80%), and right of refusal (67%). Nurses (80%) felt information disclosure was adequate, while 85% reported that patients understood disclosed information. Conclusions: Nurses practicing in local public hospitals had moderate knowledge of IC regulations. Practical implementation appeared deficient. Barriers to IC included language, workload, time constraints, lack of interpreters, and skewed gender norms in the nursing profession. Nurses require continuing professional education in healthcare law and ethics, a “corps of trained interpreters”, and gender transformation in the nursing profession to improve IC practice and overall quality of healthcare service delivery in South Africa.